Share: Handbook for artistic research education - Wilson, Mick; Ruiten, Schelte van (Amsterdam, Dublin, Göteburg ELIA, 2013)
The SHARE Handbook for Artistic Research Education is a poly-vocal document, designed as a contribution to the field of artistic research education from an organisational, procedural and practical standpoint. As a provisional disclosure of the state of the art within specific constituencies, this publication seeks to be serviceable to many different agendas and projects, and it attempts to do this by demonstrating the lived contradictions of what is simultaneously both an emerging and fully formed domain of research education. http://www.sharenetwork.eu/resources